INDIVIDUAL COUNSELING SERVICE USING CYBERCOUNSELING DURING THE COVID-19 PANDEMIC IN MAN KOTAWARINGIN TIUR - Nike Lestari (Jurnal Paedagogie Media Kependidikan, Keilmuan dan Keagamaan, 2022)
The development of the times has resulted in changes both in aspects of industrial life and all aspects of life in society, with these changes it is triggered by industrial activities that have combined the sophistication of automation technology with cyber. Cybercounseling services are very important in providing individual counseling services during a pandemic. The focus of this study is to determine the implementation of individual counseling services using cybercounseling at Madrasah Aliyah Negeri (MAN) Kotawaringin Timur during the pandemic. The methodology used in this study was descriptive qualitative, with the subject of the study being a Guidance and Counseling teacher at MAN Kotawaringin east. Data collection method using interview method, and data analysis using qualitative descriptive method. Individual counseling services are also services organized by a Guidance and Counseling teacher (counselor) to counsellors (students) in the context of alleviating personal problems of counsellors, with cybercounseling very helpful for Guidance and Counseling teachers and students during the current pandemic. Cybercuncounseling can help BK teachers to carry out their duties easily, as well as facilitate students, and so that students can make behavior changes, can also make meaningful decisions for themselves during the current pandemic.